Talking to terrorists : a personal journey from the ira to al qaeda - Taylor, Peter ([S.l.] : Harper Press, 2011)
A controversial and important book by BBC reporter and terrorism expert Peter Taylor In 'Talking to Terrorists' Peter Taylor takes us on a personal journey, quoting from diaries written at the time, as he reveals what it was like to come face-to-face with killers such as the Brighton bomber, Patrick Magee, and Islamic jihadis. What are terrorists really like? How do states counter them? And should governments talk to them? Drawing on more than 35 years of reporting terrorism, Taylor asks these questions as he tries to understand the motives of the men and women behind some of the world's most notorious terror attacks. The reality behind terrorism is complex. As the saying goes, 'one man's terrorist is another man's freedom fighter'. Many former 'terrorists' have gone on to become statesmen: Menachem Begin of Israel's Irgun, Yasser Arafat of Palestine's Fatah, Nelson Mandela of South Africa's ANC, and Gerry Adams and Martin McGuinness of Ireland's Irish Republican Army. Stripped of their masks, bombs and guns, terrorists are normal people - but they are prepared to kill in the name of a cause in which they believe. Taylor asks what lessons can be learned from the resolution of conflict in Northern Ireland in confronting the threat of Islamic extremism, and tackles head-on the highly topical issue of extracting actionable intelligence that could save lives. When does interrogation become torture? Often, he argues, there is little choice but to talk to the enemy.